2012
DOI: 10.5194/isprsarchives-xxxix-b3-403-2012
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Object Tracking With Randomized Forests

Abstract: ABSTRACT:Our work addresses the problem of long-term visual people tracking in complex environments. Tracking a varying number of objects entails the problem of associating detected objects to tracked targets. To overcome the data association problem, we apply a Trackingby-Detection strategy that uses Randomized Forests as a classifier together with a Kalman filter. Randomized Forests build a strong classifier for multi-class problems through aggregating simple decision trees. Due to their modular setup, Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To this end, Breitenstein et al (2011) suggest an on-line adaptive multi-object tracking approach using a single boosted particle-filter for each tracked individual. In (Klinger and Muhle, 2012) an on-line approach based on on-line Random Forests (Saffari et al, 2009), in which each class represents one pedestrian, is suggested for multi-object tracking.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Breitenstein et al (2011) suggest an on-line adaptive multi-object tracking approach using a single boosted particle-filter for each tracked individual. In (Klinger and Muhle, 2012) an on-line approach based on on-line Random Forests (Saffari et al, 2009), in which each class represents one pedestrian, is suggested for multi-object tracking.…”
Section: Introductionmentioning
confidence: 99%